2019
DOI: 10.1002/mrm.28134
|View full text |Cite
|
Sign up to set email alerts
|

Detection of acute kidney injury with hyperpolarized [13C, 15N]Urea and multiexponential relaxation modeling

Abstract: Twitter: @james_grist Funding information Children's Cancer and Leukaemia Group; LundbeckfondenPurpose: To assess the utility of Laplacian fitting to describe the differences in hyperpolarized [ 13 C, 15 N]urea T 2 relaxation in ischemic and healthy rodent kidneys. Methods: Six rats with unilateral renal ischemia were investigated. [ 13 C, 15 N]Urea T 2 mapping was undertaken with a radial fast spin echo method, with subsequent postprocessing performed with regularized Laplacian fitting. Results: Simulations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Hyperpolarized 13 C‐MRI is a powerful technique to noninvasively probe tissue metabolism in many normal and diseased tissues, such as brain, heart, kidneys, and cancer 4,8,25‐27 . For example, increased lactate signal has been shown to correlate with more aggressive tumors, and a reduction in this lactate is seen in a wide range of tumor models following treatment 28‐30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperpolarized 13 C‐MRI is a powerful technique to noninvasively probe tissue metabolism in many normal and diseased tissues, such as brain, heart, kidneys, and cancer 4,8,25‐27 . For example, increased lactate signal has been shown to correlate with more aggressive tumors, and a reduction in this lactate is seen in a wide range of tumor models following treatment 28‐30 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperpolarized 13 C‐MRI is a powerful technique to noninvasively probe tissue metabolism in many normal and diseased tissues, such as brain, heart, kidneys, and cancer. 4 , 8 , 25 , 26 , 27 For example, increased lactate signal has been shown to correlate with more aggressive tumors, and a reduction in this lactate is seen in a wide range of tumor models following treatment. 28 , 29 , 30 This work is now being translated into humans, and early clinical research has shown elevated hyperpolarized 13 C‐lactate in prostate cancer as well as in brain and breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For each experiment, a sample of 127 mg of [1‐ 13 C]pyruvic acid mixed with 15 mmol/L AH111501 was polarized in a SPINALIGNER (Polarize IVS, Copenhagen, Denmark) polarizer for >1.5 hours at 6.7 T at 1.3 K, to ensure a reproducible polarization of 50% on average, similar to previous reports in the SPINLAB polarizer. 30 Each mouse received over 5 seconds an intravenous injection of 100 μL per 25 g body weight of 125 mmol/L hyperpolarized [1‐ 13 C]‐pyruvate. A slice‐selective 13 C spectroscopy‐free induction decay sequence with a repetition time of 1 second, flip angle of 10°, and slice thickness of 10 mm covering the entire heart was used.…”
Section: Methodsmentioning
confidence: 99%
“…Early clinical studies have focused on the use of hyperpolarized pyruvate to probe both glycolysis and TCA metabolism for oncological, renal, and cardiac metabolism. [22][23][24][25][26][27][28][29][30][31] This review explores the application of 13 C-MRI to cerebral imaging and its future potential in the clinic.…”
mentioning
confidence: 99%